Public health approaches to practice - Mitcheson, Jan (Expanding nursing and health care practice, 2008)
Series Information Providing complete support for the developing healthcare practitioner looking to move into areas of accountability and managerial responsibility. Enhancing the knowledge and skills of health care students and registered practitioners in public health approaches to preventative health care.